2014
DOI: 10.12720/jtle.2.1.7-12
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Accidents Among Drivers in Abu Dhabi, United Arab Emirates

Abstract:  Abstract-The aim of the study was to evaluate relevant factors related to causes of Road Traffic Accidents, RTAs, among drivers in Abu Dhabi, United Arab Emirates, UAE. A questionnaire was developed and piloted in the UK and UAE. There were two versions of questionnaires distributed, one in Arabic language and the second one in English language. All respondents completed and signed a consent form which included information on their rights to withdraw from the study. Six hundred questionnaires were distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
3
14
1
Order By: Relevance
“…It has been stressed that despite the strict law on seat belt usage in UAE, a significant percentage of the drivers do not wear a seat belt either while driving or when in someone else's car. 11 We also observed that some drivers admitted not to follow driving regulations and do not use seat built.…”
Section: Discussionmentioning
confidence: 67%
“…It has been stressed that despite the strict law on seat belt usage in UAE, a significant percentage of the drivers do not wear a seat belt either while driving or when in someone else's car. 11 We also observed that some drivers admitted not to follow driving regulations and do not use seat built.…”
Section: Discussionmentioning
confidence: 67%
“…The probability that a crash will result in injury is proportional to the square of the speed. 22 More than one fifth (21.5%) of the respondents in this study had ever driven beyond their speed, even though it sees public health importance it is less as compared to other studies conducted at UAE sultanate Oman among road users (63%) 18 & Abu Dhabi among drivers (Male=47%, Female = 65%) had occasionally 13 & rarely comply with the fixed speed limit, Trinidad among drivers (67.9%) didn't always obey the speed limit. 23 Driving at excess or inappropriate speeds, while under the influence of alcohol, while sleepy or fatigued and without protective gear (such as seatbelts, child restraints, and helmets) for all vehicle occupants are major contributors to road crashes, deaths and serious injuries.…”
Section: Discussionmentioning
confidence: 72%
“…12 In this study, the prevalence of road traffic accidents is 33% which is slightly lower than the study conducted among drivers in Abu-Dhabi (49% of male and 39% of female) had a road traffic accident in the last twelve months. 13 This might be attributed to the small size of the town where this study conducted as compared to a large city like Abu Dhabi where the traffic crowd might be tenser which in-turn increases the chance of RTA occurrences & also due to the sociodemographic difference.…”
Section: Discussionmentioning
confidence: 94%
“…[ 50 ] A similar trend of pedestrian mortality has been observed in the Emirate of Abu Dhabi during 2011 and 2012, with 21% reduction in mortality by traffic related pedestrian injuries. [ 51 ] They also found majority (65%) of the pedestrian who died in RTA were of Asian origin. Despite marked reduction in pedestrian injuries and fatality in some countries, still data is lacking from other Arab Middle Eastern countries regarding the trend of traffic-related pedestrian injuries which need special attention.…”
Section: Discussionmentioning
confidence: 98%